Aplication Growth Regulator for Soybean to Increase Growth and Nutrient Uptake in Ultisols - Kartika Sry Ningsih; Mukhlis Muhklis; Jamilah Jamilah (Jurnal Agroekoteknologi, 2016)
Green house study to increase growth and nutrient uptake of soybean with giving growth regulator Benzylaminopurine (BAP) in Ultisols. Research using randomized block non factorial design with treatments: control, liming with a dose of 1,5 x Aldd (L), and 4 levels of concentration growth regulator BAP that is: 0,4 ppm (B1), 0,8 ppm (B2), 1,2 ppm (B3), dan 1,6 ppm (B4), with 4 replications. Parameter that measured is pH, root volume, root length, root dry weight, shoot dry weight, N, P, and K uptake in laboratory. Result of this research showed that growth regulator BAP are potential to  replace lime in resolving acid soil. Growth regulator BAP can increase root volume, root length, root dry weight, shoot dry weight, N, P, and K uptake better than lime. Best concentration of BAP based on this research is 0,8 ppm (B2). Keywords: BAP, Growth Regulator, Lime, Ultisols.